2017
DOI: 10.3389/fpls.2017.01406
|View full text |Cite
|
Sign up to set email alerts
|

Two FERONIA-Like Receptor Kinases Regulate Apple Fruit Ripening by Modulating Ethylene Production

Abstract: Ethylene has long been known to be a critical signal controlling the ripening of climacteric fruits; however, the signaling mechanism underlying ethylene production during fruit development is unknown. Here, we report that two FERONIA-like receptor kinases (FERLs) regulate fruit ripening by modulating ethylene production in the climacteric fruit, apple (Malus×domestica). Bioinformatic analysis indicated that the apple genome contains 14 members of the FER family (MdFERL1–17), of these 17 FERLs, MdFERL6 was exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 82 publications
1
29
0
1
Order By: Relevance
“…Zhang et al 41 . and Jia et al 42 . revealed the important role of receptor kinase during fruit ripening in strawberry and apple, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Zhang et al 41 . and Jia et al 42 . revealed the important role of receptor kinase during fruit ripening in strawberry and apple, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…The possible signaling cascades that modulate ethylene biosynthesis in climacteric fruit are poorly understood. Recently, in apple (Malus × domestica) and tomato (Solanum lycopersicum), both climacteric fruits, Feronia-like receptor kinases (FERLs) were shown to act as negative regulators of fruit ripening by inhibiting ethylene production (Jia et al, 2017). In the current study, a P. persica FERL (Prupe.6G295900), with over 75% of identity with the apple MdFERL1 and the tomato SlFERL1, was characterized as more abundant in mature than in ripe fruit (Table 1).…”
Section: Hormone Metabolismmentioning
confidence: 99%
“…FER is also essential for the expansion of leaf cells associated with brassinolide (BR) response [ 6 ] and for hypocotyl cell elongation in relation to ethylene biosynthesis [ 7 ] and signal transduction [ 8 ]. FER also regulates fruit ripening in strawberry [ 9 ] and tomato [ 10 ] via ethylene biosynthesis regulation [ 7 ]. Our recent work has shown that two FER-like receptor ( FLR ) genes in rice are crucial for cell growth [ 11 ].…”
Section: Introductionmentioning
confidence: 99%